Implementasi Pendekatan Pembelajaran â€œAbout, In, & For The Environmentâ€ dengan Model Problem-Based Learning dalam Meningkatkan Literasi Lingkungan Siswa SMA - Putri, Sevia Tasya; Nuryadin, Atin; Efwinda, Shelly (Jurnal Penelitian Pembelajaran Fisika, 2024)
Abstract. This study aims to determine the level of environmental literacy of students and the results of applying the "About, In, For the Environment" learning approach with the Problem-Based Learning (PBL) model to improve students' environmental literacy. This research is a quantitative quasi-experiment in the form of a post-test-only control group design. The population in this study were students of class XI MIPA at SMA Negeri 1 Muara Badak. The sampling technique used purposive sampling. The sample in this study involved 32 students in the control class and 33 students in the experimental class. Data collection in this study used a multiple-choice test for knowledge aspects and a statement questionnaire with a Likert scale for aspects of attention, sensitivity, attitude, and behavior. The data analysis technique used the normality, homogeneity, and Mann-Whitney U tests. The results showed that the control class obtained an average test result of 68.25% and included the low category. Meanwhile, the experimental class obtained an average test result of 81.00% and included a high category. In the Mann-Whitney U test, the Asymp. Sig. (2-tailed) of 0.000. Based on these results, it can be concluded that there is a difference between the experimental and control classes, which means that the "About, In, For the Environment" learning approach with the PBL model can improve students' environmental literacy. This approach can be an alternative to be applied in improving environmental literacy.Keywords: about, in, for the environment learning approach, problem-based learning, environmental literacy